Air pollution health research priorities for India: Perspectives of the Indo-U.S. Communities of Researchers. (October 2018) - Gordon, Terry; Balakrishnan, Kalpana; Dey, Sagnik; Rajagopalan, Sanjay; Thornburg, Jonathan; Thurston, George; Agrawal, Anurag; Collman, Gwen; Guleria, Randeep; Limaye, Sneha; Salvi, Sundeep; Kilaru, Vasu; et al.
Highlights: India has some of the highest air pollution levels in the world. Some of the sources of particulate air pollution are unique to India. Researchers have identified research priorities and Indo-US collaboration needs. Creation of national/regional databases of exposure and biological data is critical. Capacity building of scientific expertise in exposure assessment is needed.